Intertext as Countertext in Luther's Romans Lectures. Issue 1 (April 2021) - Waller, Giles
Abstract : In his article in this issue of CounterText, Brian Cummings develops an account of Luther as a counter-textual reader, in which 'iconoclastic philology' reconfigures the relation between divine and human agency, between grace and works. In response, I offer a fresh reading of the opening pages of Luther's seminal (and once long lost) Lectures on Romans, exploring the ways in which for Luther scriptural intertexts become counter-texts, at once interrupting and illuminating one another and Luther's own interpretations of them. I show that this mode of 'iconoclastic philology' unites Luther's method of reading and his theological account of grace, with each structured on a pattern of interruption.